The Impact of Transformational Leadership on Organizational Performance in the Digital Government Era - Siswadhi, Ferry; Haryono, Gampo; Lestari, Anggia Ayu; Yelnim, Yelnim (Universitas Mercu Buana, 2025)
The rapid advancement of digital government has reshaped organizational structures, decision-making processes, and leadership dynamics. This study explores the impact of transformational leadership on organizational performance in the digital government era using a qualitative research approach. Through in-depth interviews with government officials, policy analysts, and digital transformation experts, this research examines how transformational leadership traits such as vision, motivation, intellectual stimulation, and individualized consideration enhance performance, innovation, and adaptability in public institutions. Findings indicate that transformational leaders play a crucial role in fostering a culture of digital innovation, encouraging employee engagement, and driving effective change management. Leaders who exhibit proactive strategies and inspire a shared vision significantly contribute to improved public service delivery, cross-sector collaboration, and institutional resilience in navigating digital transformation challenges. Additionally, this study highlights the barriers to leadership effectiveness, including bureaucratic inertia, resistance to change, and skill gaps in digital competencies. The analysis underscores the importance of continuous leadership development programs and a supportive digital infrastructure to maximize the benefits of transformational leadership in the public sector. This study contributes to the discourse on public administration modernization by providing insights into leadership strategies that enhance government efficiency, agility, and citizen-centric service delivery. Future research should explore quantitative models to measure the correlation between transformational leadership and key performance indicators in digital governance.